Pain Perception during Laser in Situ Keratomileusis - , Khabir Ahmad, Sharmeen Akram, Salman Naveed Sadiq (Pakistan Journal of Ophthalmology, 2015)
Purpose: To compare pain severity during laser in situ keratomileusis (LASIK) between first- and second – eye surgery in a Pakistani population. Material and Methods: This was a prospective cohort study. 31 individuals eligible for LASIK in both eyes were recruited at a laser clinic between June 2012 and November 2015. All underwent surgery using microkeratome and CustomVis Solid state laser. After completion of the procedure, patients rated severity of their pain during Lasik on a 4 – point scale (e.g. none, mild, moderate, severe pain) for each eye separately. Wilcoxon signed – rank test was used to compare pain severity between first- and second – eye surgery. Results: A total of 31 patients (62 eyes) were enrolled in the study. 16 (51.6%) patients perceived more pain in the second eye and 6 (19.4%) in the first one. There were 9 (29.0%) ties. The Wilcoxon signed – rank test showed a statistically significant change in pain perception in the second eye (Z =-2.343; P = 0.019). Conclusions: Patients undergoing LASIK perceived more pain in the second eye. Larger studies are needed to investigate this finding further, and to identify factors influencing this change in pain perception.